(untitled) (Revista de Ciências Agroveterinárias, 2016)
Ocotea paranaensis is a low frequency species in the Atlantic Forest and presents occurrence records only in the state of Paraná. The present study aimed at describing and illustrating the fruit and seed morphology, germination stages and seedling of Ocotea paranaensis. The fruits used in this study were collected from 5 mother trees in Laurace State Park, Adrianópolis, PR. For the fruit and seed description and illustration, 50 random samples were analyzed. To monitor the germination stages and seedling development, 5 replicates with 10 seeds each were placed in vermiculite, and then put to germinate in a Biomatic germinator at 30 °C. The fruit is an indehiscent drupe, with coloration varying from bright green to black, with thin, hairless, smooth and shiny epicarp, quite thick, fleshy mesocarp, and smooth, coriaceous endocarp. The seed is exalbuminous, round, with smooth, membranous, with brown integument. The embryo is axial, convex flatenned of pink coloration. Germination started on the eighth day and went on up to the sixtieth day after the test was initiated. The seedling is hypogeal, cryptocotylar, presenting cylindrical epicotyl with bright green cataphylls and simple alternate protophylls, with acute apex, cuneate leaf base and light green color. The aspects described and illustrated in this study were proven to be reliable for the species identification in nurseries and also for natural regeneration studies.